Forecasting Kasus Pneumonia Untuk Kebutuhan Tempat Tidur Menggunakan Metode Triple Exponential Smooting - Dani Setiawan; Efri Tri Ardianto; Bakhtiyar Hadi Prakoso; Rossalina Adi Wijayanti (Indonesian Journal Publisher, 2024)
Pneumonia is one of the leading causes of death in the world, including Indonesia. This case is also included in the top 10 inpatient diseases at Kaliwates General Hospital, Jember Regency, and the number continues to increase from 2018 to 2022. The purpose of this study is to predict the need for hospital beds in pneumonia patients and reduce the number of hospitalized patients. This study is a quantitative descriptive study that studies the daily population survey of inpatients at Kaliwates General Hospital. The data collection technique used is documentation. The results of the study show that the days of pneumonia case care every year from 2018-2022 tend to increase and decrease repeatedly. The results of the calculation of the estimated value from actual or predicted data show that the fitted value follows the actual data pattern. In addition, the addition of beds is quite a lot needed for pneumonia cases. The suggestion that can be proposed by the researcher is that Kaliwates General Hospital is expected to be able to analyze patient care days by predicting care days in order to find out the need for beds as a reference in making decisions regarding determining bed capacity. The hospital should also plan bed needs by relocating beds from several inpatient rooms with low disease accuracy.